The Effects of Land Redistribution: Evidence from the French Revolution - Theresa Finley; Raphaël Franck; Noel D. Johnson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This study exploits the confiscation and auctioning off of Church property that occurred during the French Revolution to assess the role played by transaction costs in delaying the reallocation of property rights in the aftermath of fundamental institutional reform. French districts with a greater proportion of land redistributed during the Revolution experienced higher levels of agricultural productivity in 1841 and 1852 as well as more investment in irrigation and more efficient land use. We trace these increases in productivity to an increase in land inequality associated with the Revolutionary auction process. We also show how the benefits associated with the head-start given to districts with more Church land initially, and thus greater land redistribution by auction during the Revolution, dissipated over the course of the nineteenth century as other districts gradually overcame the transaction costs associated with reallocating the property rights associated with the feudal system.
Keywords: N53; O43; P14; D47; 330; institutions; property rights; French Revolution; Coase Theorem